ANALISIS KUALITAS PELAYANAN DI KANTIN MAITREYAWIRA MEDAN - Khowijaya, Tessya Caroline; Sutarno, Sutarno; Nugroho, Ngadjudin; Vincent, William; Cindy, Cindy (Jurnal Kajian Ekonomi dan Kebijakan Publik (JEpa); Vol 7 No 2 (2022): Jurnal Kajian Ekonomi dan Kebijakan Publik (JEpa), 2022)
Maitreyawira Canteen is a restaurant selling vegetarian food. It was established in 2015, and is located in the Cemara Asri Complex, Jalan Boulevard Utara Number 8. Deli Serdang, North Sumatra. In this study, the author took the theory of service quality from Fandy Tjiptono. The purpose of this study is to determine the quality of service in the Maitreyawira Canteen. The author uses descriptive qualitative research methods. The data sources used by the authors are primary and secondary data. The authors used data collection techniques with field research (interviews). From the results of research conducted by the author shows that the quality of service carried out by the Maitreyawira Canteen is still lacking, customers still feel disappointed with the service provided.